Analisis Kinerja Fasilitas Pejalan Kaki di Pusat Perbelanjaan Kota Padang - Miro, Fidel (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2011)
The walking facilities in Pasar Raya and Permindo corridor not using effectively. Uneffective is caution the facility condition still not representative of quantity or quality and supply of facilities unstandarize with pedestrian behavior. The objective research is analysis performance of the walking facilities on a long this corridor based characteristic pedestrian behavior, perception and preferences walkers for facilhj supply. The Aproach metlwde in this research is: Identify pedestrian behavior, perception and preferences walkers. Evaluation performaces walking facilities supply. Knowledge the demand side for quantity walking facilities by measurement pedestrian traffic flaws. Someone inffiuences of pedestrians behavior is follow; walking facility dimention must can be capacity walkers with together 2 to 3 persons or more, walkers do not like trade informal (PKL) on walking path (trotoar), walker will be change to roads, if walking path is inconnection, pedestrian not using zebra cross caution is the near path. Tize basic this variables and the supply facilities equal with satndarize, pedestrian areas must free of inconnecting and accessibility mobile in this area. Tiw big qonsequency in aplly this reseach of pedestrian facilities performance is take areas from people to increase dimention of trotoar for can be capasity of pedestrian traffic flows. Other analysis about increase capasity of pedestrian facility, special for supply unstandarized. Pedestrian facility influence of pedestrian desire, hope using facility walkers increase and central bussiness distric areas becomes high economic for Padang.Key Words: Performance, Pedestrian Facility and Central Bussiness Distric.